Visual Fixation and Continuous Head Rotations Have Minimal Effect on Set-Point Adaptation to Magnetic Vestibular Stimulation - Ward, Bryan K.; Zee, David S.; Roberts, Dale C.; Schubert, Michael C.; Pérez-Fernández, Nicolas; Otero-Millan, Jorge (Frontiers in Neurology, 2019)
Background: Strong static magnetic fields such as those in an MRI machine can induce sensations of self-motion and nystagmus. The proposed mechanism is a Lorentz force resulting from the interactions between strong static magnetic fields and ionic currents in the inner ear endolymph that causes displacement of the semicircular canal cupulae. Nystagmus persists throughout an individual’s exposure to the magnetic field, though its slow-phase velocity partially declines due to adaptation. After leaving the magnetic field an after effect occurs in which the nystagmus and sensations of rotation reverse direction, reflecting the adaptation that occurred while inside the MRI. However, the effects of visual fixation and of head shaking on this early type of vestibular adaptation are unknown. Methods: Three-dimensional infrared video-oculography was performed in six individuals just before, during (5, 20, or 60 minutes) and after (4, 15, or 20 minutes) lying supine inside a 7T MRI scanner. Trials began by entering the magnetic field in darkness followed 60 seconds later, either by light with visual fixation with head still, or by continuous yaw head rotations (2Hz) in either darkness or light with visual fixation. Subjects were always placed in darkness 10 or 30 seconds before exiting the bore. Results: In darkness with head still all subjects developed horizontal nystagmus inside the magnetic field, with slow-phase velocity partially decreasing over time. An after effect followed on exiting the magnet, with nystagmus in the opposite direction. Nystagmus was suppressed during fixation; however, after resuming darkness just before exiting the magnet, nystagmus returned with velocity close to the control condition and with a comparable after effect. Similar aftereffects occurred with continuous yaw head rotations while in the scanner whether in darkness or light. Conclusions: Visual fixation and sustained head shaking either in the dark or with fixation inside a strong static magnetic field have minimal impact on the short-term mechanisms that attempt to null unwanted spontaneous nystagmus when the head is still, so called VOR set-point adaptation. This contrasts with the critical influence of vision and slippage of images on the retina on the dynamic (gain and direction) components of VOR adaptation.